A STUDY OF THE DYNAMICS ANTHOCYANINS ACCUMULATION IN BLACK HAWTHORN SPREAD IN GEORGIA - Aleksandre Chalatashvili; Mariam Khositashvili; Zaza Baazov (European Journal of Agricultural and Rural Education, 2022)
There are several species of hawthorn in Georgia, the most important from them is black hawthorn with its healing properties and content of biologically active substances. Black hawthorn is a bushy plant representative of the hawthorn rose family. Information about this plant can be found in the works of Greek philosophers, as far back as the fourth century AD. The biochemical composition of the fruit and flower of the plant is of great interest to scientists because of its medicinal, prophylactic and dietary value. Although black hawthorn has been used in folk medicine for quite long time, the chemical composition of its fruit has not been thoroughly studied. It is known to contain flavonoids: quercetin, camperol, apigenin, herbacetin, 3- methoxyherbacetin and their glycosides: orientin, vitexin, saponaren. The fruit contains anthocyanins, leukoanthocyanidins, phenolic carbonic acids, organic acids, ascorbic acid, pectin, sugar. The use of black hawthorn in folk medicine began 5 centuries ago. It was used for treatment of diarrhea and dysentery. Hawthorn flower decoction was used as a blood purifier, and later began to be taken in diseases of the cardiovascular system. Hawthorn flavonoids are characterized by antioxidant activity. From the chemical substance, that are composed in black hawthorn the one of the most iprotant is Anthocyanins. Anthocyanins are water-soluble pigments that cause different colors of the plant.